CONCEPT OF JUSTICE IN THE MANAGEMENT OF NATURAL RESOURCES - Yanis Rinaldi (Jurnal Dinamika Hukum, 2015)
The concept of justice which is formulated into a principle of justice in the laws of natural resources has not accommodate global principles, ethical view, and the values that live in the community. This study aims to find the concept of justice in the management of natural resources. The concept was excavated from the global principles of natural resource management, ethical views of society, and customary law. Method to find the concept of normative-legal approach research. The findings of the research, the concept of justice in the management of natural resources containing at least six basic principles, namely: intragenerational and intergenerational principle, the principle of the protection of human rights, gender equality, recognition of customary law community, proportionality obtaining benefits with recovery obligations, and balance gain access and results. The concept of justice is in line with the global principles of natural resource management, ethical view, and customary law.Keywords: concept of justice, management, natural resources.